The Curative Activity of Isolated Fraction from Spathodea campanulata Beauv Stem Bark on Rats Exposed to Benzopyrene - Masruri Masruri; Mohamad Lutfillah; Ady Sumaryanto; Rurini Retnowati; Aulanni'am Aulanni'am (Journal of Tropical Life Science, 2014)
This paper reports a screening results of the secondary metabolites composed in Spathodea campanulata Beauv stem bark, evaluate inhibiting activity of malondialdehyde (MDA) on rats cancer model exposed with benzopyrene, and the histology of its lung. The secondary metabolite of the stem bark fraction consisted of alkaloids, flavonoids-phenolic, terpenoid and steroid compounds. The isolated fraction contained of these metabolites significantly indicate bioactivity by reducting of malondialdehyde (MDA) level, and also histology appearance of the lung tissue prepared from the benzopyrene-exposed rat indicated a curative activity.